PENINGKATAN POTENSI PARIWISATA ALAM BUTTA TOA ADALAH JEMBATAN UNTUK MENYEJAHTERAKAN MASYARAKAT DALAM WUJUD RANCANGAN PERATURAN DAERAH - Akhyuning, Andi Rismunadia; Fattah, Sulaeman (Politeknik STIA LAN Makassar, 2024)
Tourism is a critical component of national development that significantly enhances the well-being of the community and contributes to economic growth. Nature tourism is a category of tourism that is in high demand among the general public. Bantaeng Regency is one of the regions with significant tourism potential, particularly natural tourism, due to its strategic geographical location. However, the majority of the natural tourist destinations are not currently under government management, and it would be regrettable if the potential were to be neglected. Consequently, it is imperative that the government realize the potential of tourism in order to enhance the well-being of the community and preserve the wealth of existing resources. The objective of this study was to develop and consolidate the Bantaeng Regency Regional Regulation Draft as a solid foundation for the development of public policies that will enhance the potential of tourism. This draft will serve as a guide for the planned regulation and implementation of tourism. In the preparation of this academic paper, normative juridical and empirical juridical methods are employed, with qualitative data collection methods, including literature evaluations and interviews with all pertinent stakeholders. The result of study are presented in an academic paper that has been drafted in compliance with the enactment of laws and regulations, as well as with the current laws and regulations.